Evidence based responsible use of antibiotics in companion animals. ([2013]) - Boulouis, Henri-Jean; Caney, Sarah; Cotard, Jean-Pierre; Dupre, Gilles; Farca, Anna Maria; Fontaine, Jacques; Kietzmann, Manfred; Lechowski, Roman
No abstract available